Single-chain antibody fragments: Purification methodologies - Pellegrini Malpiedi, Luciana (2013)
At present, single-chain variable fragments (scFv) of antibodies are considered one of the most important tools in human therapies. Wide applications of antibodies are being exploited in different medical, pharmaceutical and research areas. These molecules maintain the same binding functionality that full length antibodies but possess several advantageous features as quickness to penetrate the tissues, easy manipulation, fast elimination of their immunocomplex and the possibility of being produced in simple expression systems like bacteria and yeast. The increasing demand in antibody based methodologies is driving advances in the production and purification of genetically engineered antibodies and antibody fragments. While advances in expression systems allow the production of high titers of antibodies, there exist some limits imposed by the downstream methodologies which are not efficient enough to ensure their industrialization. The main aim of this review is to highlight the principal characteristics of single-chain variable fragments of antibodies addressing advances and perspectives on scFv purification.